Recursion Example Two
Defining Rule

t1 = 3

tn = 2tn-1


Generating the Sequence

Knowing that the first terms is three (t1 = 3), calculate the value of the second term (t2)

Since we need to calculate t2, substitute n = 2 into the second part of the recursive rule (tn = 2tn-1)


      t(2) = 2t(2)-1

      t2 = 2t1                  (But it is known that t1 = 3)

      t2 = 2(3)

      t2 = 6


Repeat this process to find t3.

Knowing that the first two terms are three and six (t1 = 3 and t2 = 6, calculate the value of the third term (t3)

Since we need to calculate t3, substitute n = 3 into the second part of the recursive rule (tn = 2tn-1)


      t(3) = 2t(3)-1

      t3 = 2t2                  (But it was calculated that t2 = 6)

      t3 = 2(6)

      t3 = 12


Repeat this process to find t4.

Knowing that the first three terms are three, six and twelve (t1 = 3, t2 = 6 and t3 = 12), calculate the value of the fourth term (t4)

Since we need to calculate t4, substitute n = 4 into the second part of the recursive rule (tn = 2tn-1)


      t(4) = 2t(4)-1

      t4 = 2t3                  (But it was calculated that t3 = 0)

      t4 = 2(12)

      t4 = 24


Repeat this process to find as many terms as required.


Sequence: 3, 6, 12, 24, 48, 96, 192, . . .

Sequence: Starting with three, multiply each term of the sequence by two to determine the next term of the sequence.